SISTEM PENILAIAN KINERJA TENAGA PENDIDIK DALAM BIDANG PEMBELAJARAN DENGAN 360 DEGREE FEEDBACK - Ika Rachmawati; Anna Widayani (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
Abstract: Akademi Komunitas Negeri Putra Sang Fajar Blitar (AKB) is a state higher education institution that organizes vocational education. Educators at AKB consist of lecturers and instructors. This study examined the function of a 360-degree feedback performance appraisal system to determine the performance of educators in the field of learning which included aspects of preparation, implementation of learning activities, and evaluation of learning outcomes. Performance appraisal ere carried out by filling out performance appraisal forms by parties who were stakeholders of the teaching staff, i.e: students as consumers, study program coordinators as supervisors, educators as peers, and the academic section as collaborators. The performance appraisal form contained a set of questions for which the assessor can provide an assessment based on a rating scale of 1-4 (graphic rating scale), with very good, good, good enough, and not good criteria. The result shows that the performance of teaching staff in AKB based on time criteria, tidiness, communication, lecture processes, mastery of the material and evaluation of learning was very good, although there were still a few things that need to be improved, such as timeliness in submitting scores ​​and firmness in enforcing dicipline to the students who are not orderly.